Investigating the effect of CEO experience and board size on capital structure in companies listed on the Tehran Stock Exchange - Zeinab AsadollahZadeh (New Applied Studies in Management, Economics & Accounting, 2020)
This study aims to investigate the effect of CEO experience and board size on capital structure. This research is empirical and correlation. In this study, 147 companies listed on the Tehran Stock Exchange were selected as a sample, and their financial statements over a period of 5 years from 2014 to 2019 were studied. In order to formulate the theoretical foundations and concepts, the secondary study method has been used. Also, financial data were collected using modern management and forecasting software and were prepared for analysis in Excel software. The research hypotheses were tested using Eviews software. The results indicate that there is no significant relationship between CEO experience and board size with capital structure.